Religious Values in Hijaz Yamani Poetry: Integration of Spiritual Responsibility in Character Education - Hidayat Putra, Muhammad Adhitya; Malihah, Elly; Wiyanarti, Erlina; Darmawan, Wawan (Universitas Islam Negeri Madura, 2025)
This study aims to describe and analyze religious values ​​and spiritual responsibility in Hijaz Yamani poems and their relevance to character education in learning. The study used a descriptive qualitative method with a content analysis approach. Data were sourced from the poetry anthology “Malam Hujan” with data collection techniques through literature study, observation, and notes. The results of the study indicate that: (1) Religious values ​​in Hijaz Yamani poems are integrated with spiritual responsibility values ​​reflected through the use of diction, symbols, and figures of speech that represent the vertical relationship between humans and God; (2) The poem “Kalau Kau Datang” contains spiritual responsibility values ​​shown through awareness of the presence of angels as a symbol of the end of life and readiness to face the Creator; (3) Religious values ​​and spiritual responsibility in Hijaz Yamani poems have significant relevance to character education, especially in the development of students’ spiritual, moral, and social dimensions. The implication of this study is the importance of integrating religious values ​​and spiritual responsibility through literary works in learning to strengthen students' character education.